Kunjungan Lebah Tukang Kayu Xylocopa confusa Linn (Hymenoptera: Anthophoridae) Pada Pertanaman Terong di Kelurahan Dadok Tunggul Hitam Kecamatan Koto Tangah Padang - Novia, Elvia - (Pendidikan Biologi, 2014)
Xylocopa an insect that has a habit of life makes a nest on a tree that is known as the carpenter bee, Xylocopa nests are usually made of softwood, hardwood and especially on weathered wood. Xylocopa have thick body hair on the thorax, which makes Xylocopa as insect pollinators. This study aims to determine the traffic carpenter bee Xylocopa confusa (Hymenoptera: Anthophoridae), the planting of eggplant in Kelurahan Dadok Tunggul Kecamatan Koto Tangah Padang. This study was conducted in March 2014 with a descriptive survey method is by direct observation of activities Xylocopa confusa on-site research. Observations were carried out in the field at planting eggplants two months old. Physical environmental factors measured are temperature, humidity, and wind speed. The area is used as a study of about 10 x 8 m. The results showed that the number of visits Xylocopa confusa on eggplant crop in Kelurahan Dadok Tunggul Hitam Kecamatan Koto Tangah Padang there is the highest at 07.00 and 08.00, with the average number of visits 16:57 tails, and the lowest number of visits Xylocopa confusa at 13:00 pm , the number of visits an average of 1.43 birds. While the number of Xylocopa confusa the highest out of the eggplant crop there at 07:00 pm, with an average of 11.71 tails, and the number of out Xylocopa confusa lowest at 13.00 pm, with the average number of 1.14. Number of flowers visited by Xylocopa confusa there in the morning with an average of 15.47 and a little flower Xylocopa confusa reached there in the afternoon with an average rate of 6.71.